Effect of braiding angle on progressive failure and fracture mechanism of 3-D five-directional carbon/epoxy braided composites under impact compression. (1st December 2019) - Cui, Can; Dong, Jiwei; Mao, Xianbiao
Abstract: At present, there are few systematic studies on dynamic mechanical response of 3-D braided composites according to different braiding angles. In this paper, the mechanical properties, real-time progressive failure law and fracture mechanism of 3-D five-directional braided composites at different braiding angles are systematically studied by using SHPB test apparatus. The results show that braiding angle is an important factor affecting the mechanical properties of composites, which under smaller braiding angle are higher, and the longitudinal mechanical properties of composites are more sensitive to braiding angle. In particular, the material still has a certain post-peak bearing capacity after longitudinal impact, presenting a nonlinear change trend of first increasing and then decreasing. The high-speed photographs and stress-strain curves show that different braiding angles reflect the degree of progressive failure of composites, and different loading patterns reveal the morphology of progressive failure of composites. With the increase of braiding angle, the braiding structure changes greatly, which leads to gradual serious progressive failure of composites. This point is also confirmed from the perspective of macroscopic failure characteristics and microscopic fracture morphology.